Tumor Lysis Syndrome in Chronic Lymphocytic Leukemia with Novel Targeted Agents. (29th August 2017) - Cheson, Bruce D.; Heitner Enschede, Sari; Cerri, Elisa; Desai, Monali; Potluri, Jalaja; Lamanna, Nicole; Tam, Constantine
Abstract: Tumor lysis syndrome (TLS) is an uncommon but potentially life‐threatening complication associated with the treatment of some cancers. If left untreated, TLS may result in acute renal failure, cardiac dysrhythmia, neurologic complications, seizures, or death. Tumor lysis syndrome is most commonly observed in patients with hematologic malignancies with a high proliferation rate undergoing treatment with very effective therapies. In chronic lymphocytic leukemia (CLL), historically, TLS has been observed less often, owing to a low proliferation rate and slow response to chemotherapy. New targeted therapies have recently been approved in the treatment of CLL, including the oral kinase inhibitors, idelalisib and ibrutinib, and the B‐cell lymphoma‐2 protein inhibitor, venetoclax. Several others are also under development, and combination strategies of these agents are being explored. This review examines the diagnosis, prevention, and management of TLS and summarizes the TLS experience in CLL clinical trials with newer targeted agents. Overall, the risk of TLS is small, but the consequences may be fatal; therefore, patients should be monitored carefully. Therapies capable of eliciting rapid response and combination regimens are increasingly being evaluated for treatment of CLL, which may pose a higher risk of TLS. For optimal management, patients at risk for TLS require prophylaxis and close monitoring with appropriate tests and appropriate management to correct laboratory abnormalities, which allows for safe and effective disease control. Abstract : Tumor lysis syndrome is an uncommon but potentially life‐threatening complication associated with the treatment of some cancers. In this review, prevention strategies and management of patients with chronic lymphocytic leukemia who develop tumor lysis syndrome are described.